2012
DOI: 10.1136/jech-2011-200590
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Community Ownership and Preparedness Index: using data to inform the capacity development of community-based groups

Abstract: BackgroundCommunity mobilisation is an important component of a participatory approach to health and development interventions. However, it is challenging to define, measure and assess community participation and ownership of a programme, especially at scale.MethodsAn iterative cross-sectional survey was designed for implementation across a representative sample of community-based groups, using a weighted index that captured both qualitative and quantitative data in a standardised form. These data were aggrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 39 publications
1
33
0
Order By: Relevance
“…The overall index scores calculated determined the strength of community mobilisation, and the scores were grouped into a series of ‘bands’ labelled Basic (0–14), Foundation (15–29), Promising I (30–43), Promising II (44–57), Promising III (58–72), Vibrant I (73–87) and Vibrant II (88–100). Details of the interview tools, calculation of index scores and interpretation of the series of bands are discussed in the article by Thomas et al 15 in this volume.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall index scores calculated determined the strength of community mobilisation, and the scores were grouped into a series of ‘bands’ labelled Basic (0–14), Foundation (15–29), Promising I (30–43), Promising II (44–57), Promising III (58–72), Vibrant I (73–87) and Vibrant II (88–100). Details of the interview tools, calculation of index scores and interpretation of the series of bands are discussed in the article by Thomas et al 15 in this volume.…”
Section: Methodsmentioning
confidence: 99%
“…The COPI study was analysed, and the index scores were calculated using the analytical tool developed by Praxis and published in this volume 15. The percentage distributions from an independent FSWs survey conducted in the select districts were calculated for each measure of collective efficacy, collective agency and collective action.…”
Section: Methodsmentioning
confidence: 99%
“…Involvement of community members not only ensured that indicators moved from being purely healthbased and HIV-related to being more reflective of the totality of the everyday experience of stigma, discrimination and denial. Community members' perspectives on the relative significance of each indicator in the larger community mobilization framework were also taken into account (Thomas et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Where CBOs had been set up, elected representatives would meet monthly at the district levels and take responsibility for matters such as membership fees and, ultimately, for strategic planning (cf. Thomas et al, 2012).…”
Section: The Avahan Initiativementioning
confidence: 99%
“…According to Thomas, Narayanan, Wheeler, Kiran, Joseph and Ramanathan (2012), the extent to which community participate in developmental plans is crucial to sustainability of that project. The findings showed that community participation play significant role in achieving sustainable human development as indicated in the figure 1 below.…”
Section: Impediment To Sustainable Human Development In the Niger Deltamentioning
confidence: 99%